Factors Affecting Behavior Sex On Boarding Children In Tosaren Village Islamic Boarding School District, Kediri City - Olifas Benu; Ema Mayasari (Universitas STRADA Indonesia, 2019)
Premarital sexual behavior among teenagers is increasing. Teenagers' great curiosity, developments in information technology, lack of communication within the family, and society's increasing ignorance make this behavior increasingly widespread. The aim of this research is to find out the factors that influence the sexual behavior of boarding school children. The research design is quantitative analytical with a cross sectional design. The population is all boarding school children in Tosaren Village, Islamic Boarding School District, Kediri City aged 21-24 years with a total population of 120 teenagers, a sample of 70 respondents using a purposive sampling technique. The data collection technique uses a questionnaire. The results showed that the majority of respondents who were male had positive sexual behavior as many as 27 respondents (73.0%), the majority of respondents with tertiary education had positive sexual behavior as many as 47 respondents (85.5%), respondents who had good knowledge all had positive sexual behavior as many as 43 respondents (100%) and respondents who had a positive attitude almost all had positive sexual behavior as many as 59 respondents (93.7%). Based on the results of the Multiple Logistic Regression analysis, it shows that with a p-value of 0.000 < 0.05, H1 is accepted so it can be concluded that simultaneously there is an influence of gender, education, knowledge and attitudes on sexual behavior among boarding school children in Tosaren Village, Islamic Boarding School District, Kediri City with the magnitude of the effect is 88.1%. In general, adolescents in middle and late age are vulnerable to engaging in dangerous and high-risk behavior, such as narcotics abuse or unprotected sexual relations. Parents are expected to provide early education and pay more attention to their children who are in their teenage years or when they are away from them.